Pemberdayaan Lansia dalam Pencegahan Hipertensi melalui Skrining dan Edukasi di Dusun Grujugan - Rahsunji Intan Nurvitasari (Jurnal Pengabdian Masyarakat Waradin, 2025)
Hypertension is a Non-Communicable Disease (NCD) whose prevalence continues to increase from year to year, especially in the elderly. This condition is a serious challenge in the field of public health because hypertension can increase the risk of cardiovascular disease, stroke, and kidney failure if not properly managed. The high incidence of hypertension in the community, especially in Grujugan Hamlet, RT. 07–10, Bantul Village, has become a concern in community-based promotive and preventive efforts. Therefore, this community service activity aims to increase the knowledge and awareness of the elderly about hypertension through a direct screening and health education approach. The implementation method includes blood pressure checks (initial screening), counseling using educational media such as leaflets, posters, and interactive presentations, and evaluation of understanding through filling out pre- and post-tests. A total of 24 elderly people participated as respondents in this activity. The screening results showed that the majority of participants (62.5%) were in the Hypertension Level 2 category, while the other 8.3% were in the Hypertension Crisis category. Before the education, pre-test results showed that 58.3% of elderly people had low knowledge about hypertension. However, after the education, 75% experienced an increase to a high level of knowledge. Statistical analysis using the Wilcoxon Signed Rank test showed a significant difference between pre-test and post-test scores (p < 0.001), indicating that the health education provided was effective in improving participants' understanding. This activity has had a positive impact on improving health literacy and can serve as the basis for developing sustainable, community-based, participatory hypertension prevention programs.